Methodologies for Backbone Macrocyclic Peptide Synthesis Compatible With Screening Technologies - Shinbara, Koki; Liu, Wenyu; van Neer, Renier Herman Pieter; Katoh, Takayuki; Suga, Hiroaki (Frontiers in Chemistry, 2020)
Backbone macrocyclic structures are often found in diverse bioactive peptides, and contribute to conformational rigidity, peptidase resistance, and potential membrane permeability compared to their linear counterparts. Therefore, such peptide scaffolds are an attractive platform for drug-discovery endeavours. Recent advances in synthetic methods of backbone macrocyclic peptides have enabled discovery of novel peptide drug candidates against diverse targets. Here, we overview recent technical advancements of the synthetic methods including enzymatic and chemical synthesis, split-intein circular ligation of peptides and proteins (SICLOPPS), and genetic code reprogramming. We also mention the later three of synthetic methodologies compatible with screening methodologies such as one-beads one-compound (OBOC) screening, cell-based assay, limiting-dilution PCR, and mRNA display.